Perkawinan di Bawah Umur pada Masa Pandemi Covid-19 Perspektif Perubahan Sosial (Studi Kasus di Kabupaten Ponorogo) - Uswatul Khasanah; Agus Purnomo (Journal of Economics, Law, and Humanities, 2022)
The Covid-19 pandemic has had an impact on the social sector. One of the smallest institutions in the social system that is affected is the family, namely the occurrence of underage marriages. Based on data released by the Religious Courts Agency, the phenomenon of child marriage has tripled. In 2019 there were 23,126 cases, and in 2020 it increased to 64,211 cases. This increase in underage marriage also occurred in Ponorogo Regency. Based on data from the Ponorogo Regency PA, in 2019 there were 97 cases, and in 2020 it increased to 235 cases. From exposure to these facts, this study aims to analyze the impact of social changes due to the Covid-19 pandemic on the increase in underage marriage in Ponorogo Regency, analyze the form of social processes due to the Covid-19 pandemic on the increase in underage marriage in Ponorogo Regency, and analyze the role of agents of social change in the increase in underage marriage due to the Covid-19 pandemic in Ponorogo Regency. This research includes field research, with qualitative methods and a sociological approach. The results of this study can be concluded that first, there are social changes due to the Covid-19 pandemic which have an impact on increasing underage marriage in Ponorogo Regency, which includes three aspects, namely structure, family function, and environment. Second, the form of the social process of change above is social development. Third, there is a change in the role of the community as agents of social change due to the Covid-19 pandemic which has an impact on increasing underage marriages.